Valuasi Ekonomi Kawasan Birdwatching Repang Muaif - Marsi Adi Purwadi; Hendra Kurniawan Maury (UNIVERSITAS CENDERAWASIH, 2019)
The objectives of the activities of the Economic Evaluation of the Repang Muaif Birdwatching Area in Jayapura Regency are to: 1) Increase the knowledge and understanding of the community about the functions and roles of the Repang Muaif Birdwatching Zone in Jayapura Regency; 2) The creation of an equal role of the community in the development of the Repang Muaif Birdwatching Area in Jayapura Regency. The area to be carried out in the study area is the Economic Valuation of the Repang Muaif Birdwatching Area in Jayapura Regency. Where the results of the implementation of science and technology are from the results of the pree test conducted, it was found that out of 21 participants who attended this training, 76.19 percent of participants did not understand the concepts and rules regarding the economic valuation of forest ecosystems. While the rest, which is as much as 23.81 percent, have known the concepts and rules related to the economic valuation of forest ecosystems. Whereas from the post test results, it was found that out of 21 participants who attended this training, 15.08 percent of the participants still did not understand the concepts and rules regarding the economic valuation of forest ecosystems. While the rest, which is as much as 84.92 percent have known the concepts and rules related to the economic valuation of forest ecosystems. In addition, the participation of the community in forest conservation is very important, it can be seen from the many participants who want to attend this training activity. Where of the 25 participants planned as participants in this training, 21 participants attended the training and 4 participants did not take part in the training.